Partisipasi Warga Melalui Media Digital dan Implikasinya terhadap Akuntabilitas serta Perumusan Kebijakan Pemerintah Daerah di Lampung - Ulfa Umayasari; Amantha, Goestyari Kurnia (Journal of Administration, Governance, and Political Issues, 2025)
This study examines the phenomenon of citizen participation through digital media and its implications for accountability and regional policy formulation in Lampung Province. Starting from the rapid penetration of the internet and the digitalization of regional government services, this study explores the opportunities and challenges of e-participation to expand transparency, responsiveness, and the quality of regional governance. Using literature study methods and secondary data analysis, this study answers questions about the urgency of digital participation, theoretical foundations related to e-governance and digital democracy, an overview of the phenomenon of digital participation of Lampung citizens, and policy recommendations for strengthening regional accountability. The results of the study show that digital participation in Lampung has grown significantly, as seen from the example of the virality of citizen criticism regarding infrastructure that triggered responses from regional and central governments. Digital participation also has a positive impact on increasing transparency and the quality of regional policies. However, challenges related to digital literacy, technological gaps, and bureaucratic resistance still need to be anticipated so that digital civic engagement can grow inclusively and have a real impact on regional government.